Comparative effectiveness of bisphosphonate treatments for the prevention of re-fracture in glucocorticoid-induced osteoporosis: protocol for a systematic review and meta-analysis. Issue 9 (26th September 2022) - Chu, Hongmin; Jang, Bo-Hyoung; Kim, GaYoon; Bae, Seowoo; Lee, Hyeju; Nam, Seonghee; Ahn, Jeonghoon
Abstract : Background: Long-term usage of glucocorticoids results in a loss of bone mass and a higher risk of fracture, and the most common cause of secondary osteoporosis is glucocorticoid-induced osteoporosis (GIOP). For preventing GIOP, bisphosphonate (BP) is widely used. However, analysis on BP's effect on the prevention of re-fracture is insufficient. The purpose of the present study is to evaluate the comparative treatment effect and prevention of re-fracture according to the type of BP in GIOP as the basis for a reliable clinical strategy for patients. Methods and analysis: We will search electronic databases of the PubMed, Cochrane Library and EMBASE using a comprehensive search strategy in December 2021 with no language restriction. Randomised controlled trials (RCTs), quasi-RCTs, controlled trials and cohort studies evaluating the effectiveness of BP to the patients with GIOP will be included in this study. The primary outcome will be the incidence of hip, vertebral and other fractures. The secondary outcome will include percentage changes on the bone mineral density and incidence of re-fracture. Assessing risk of bias for included studies is done using the Cochrane Risk of Bias tool and Risk Of Bias In Non-randomized Studies–of Intervention tool. If quantitative synthesis is possible, a meta-analysis will be performed. A subgroup analysis will be conducted to compare re-fracture rate on the patients with GIOP who experience previous fractures. This study's result will provide evidence for the effectiveness of BP in the prevention of re-fracture on patients with GIOP. Ethics and dissemination: The results will be disseminated through publishing in a peer-reviewed journal or public presentations. Ethical approval is not required as this is a systematic review of publicly available data. PROSPERO registration number: CRD42022343787.